2020
DOI: 10.1186/s13071-020-04456-w
|View full text |Cite
|
Sign up to set email alerts
|

First report on the phylogenetic relationship, genetic variation of Echinococcus shiquicus isolates in Tibet Autonomous Region, China

Abstract: Background Cystic or alveolar echinococcosis caused by the larval stages of Echinococcus spp. is a very severe zoonotic helminth infection. Echinococcus shiquicus is a newly discovered species that has only been reported in the Qinghai and Sichuan provinces of the Qinghai-Tibet plateau, China where, to date, it has only been confirmed in Tibetan foxes and wild small mammal populations of the Tibetan plateau. Information on its genetic and evolutionary diversity is scanty. The aim of this study was to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…In this report, analyses of the concatenated mitochondrial cox1 and nad1 gene sequences were used to infer the population structure of E. shiquicus collected from the plateau in contrast to most previous studies that utilized partial gene sequences. The E. shiquicus population, as seen in the neutrality indices demonstrated by the cox1 and concatenated cox1-nad1 genes, suggested population expansion with significant negative values of Fu's F. This observation is in contrast to the population indices observed in some previous studies in Qinghai and Sichuan provinces where the neutrality test demonstrated positive nonsignificant values based on partial cox1 gene as well as a recent investigation of E. shiquicus populations from the Tibet Autonomous Region and Qinghai Province although with a longer DNA fragment, 2505 bp (Nakao et al, 2010;Zhu et al, 2020). With the geographically isolated and harsh climatic conditions of the plateau, one would expect that E. shiquicus population in the plateau would have experienced a population bottleneck event considering the geological events that led to the formation of the plateau millions of years ago (Harrison et al, 1992), but with the contrasting available reports mainly based on short gene sequences, the population structure and demographic history of E. shiquicus across the plateau remain to be further explored and it would be interesting to understand the population structure vis-à-vis the timeline of events during the plateau formation.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…In this report, analyses of the concatenated mitochondrial cox1 and nad1 gene sequences were used to infer the population structure of E. shiquicus collected from the plateau in contrast to most previous studies that utilized partial gene sequences. The E. shiquicus population, as seen in the neutrality indices demonstrated by the cox1 and concatenated cox1-nad1 genes, suggested population expansion with significant negative values of Fu's F. This observation is in contrast to the population indices observed in some previous studies in Qinghai and Sichuan provinces where the neutrality test demonstrated positive nonsignificant values based on partial cox1 gene as well as a recent investigation of E. shiquicus populations from the Tibet Autonomous Region and Qinghai Province although with a longer DNA fragment, 2505 bp (Nakao et al, 2010;Zhu et al, 2020). With the geographically isolated and harsh climatic conditions of the plateau, one would expect that E. shiquicus population in the plateau would have experienced a population bottleneck event considering the geological events that led to the formation of the plateau millions of years ago (Harrison et al, 1992), but with the contrasting available reports mainly based on short gene sequences, the population structure and demographic history of E. shiquicus across the plateau remain to be further explored and it would be interesting to understand the population structure vis-à-vis the timeline of events during the plateau formation.…”
Section: Discussioncontrasting
confidence: 81%
“…It was also, detected around Qinghai Lake in Ganzihe town of Haiyan County and Gonggongma village of Gangcha County towards the northeastern edge of the plateau. Until now, the diversity and population structure of E. shiquicus has been largely investigated by partial mitochondrial gene sequences of cox1 and/or nad1 (Ma et al, 2012(Ma et al, , 2015Wang et al, 2018;Han et al, 2019), and recently by mtDNA sequences of up to 2505 bp (Fan et al, 2016;Zhu et al, 2020). Moreover, studies have shown that by analysing longer DNA sequences or certain genes with higher resolution power, a better understanding of the intraspecies variation and phylogenetic resolution of Echinococcus species is realised (Laurimäe et al, 2018(Laurimäe et al, , 2019Ohiolei et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Near-complete/complete mtDNA could be considered in areas with multiple species and genotypes such as TAR to identify the accurate species and genotypes among patients who need surgery to remove the lesion when the differential diagnosis such as imaging or qPCR is not conclusive. No E. shiquicus infection was identified with either qPCR or mtDNA method, which confirmed that humans were probably insusceptible to E. shiquicus , a new species found in the Tibetan Plateau only, despite the concern of its potential, given dog infection of E. shiquicus was reported [ 65 ]. Besides, near-complete/complete mitochondrial sequences of patients could serve as baseline data to monitor the Echinococcus species and genotype prevalence changes, mtDNA mutations, and trends of Echinococcus spp.…”
Section: Discussionmentioning
confidence: 76%